Factors Affecting Operation Information Systems: Strategy, Software, Human Resources - Harum, Kamelinia Magda; Hapzi Ali (Dinasti International Journal of Digital Business Management, 2022)
Operation information systems are a tool that is needed by companies and government agencies in processing databases obtained from and used in the company's business. Literature review article Factors Affecting Operation Information Systems: Strategy, Software, and Human Resources are scientific article that aims to build a research hypothesis of the influence between variables that will be used in future research, within the scope of the Executive Support System for Business. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other academic online media. The results of this article are that: 1) Strategy affects operation Information systems; 2) Software affects operation information systems, and 3) Human Resources influence the operation information systems.